Sohar Ancient Fields Project: Interim Project no. 1 - Wilkinson, T. J. (The Journal of Oman Studies, 1975)
During surveys conducted in 1973 as part of the Harvard Archaeological Survey of Oman, Williamson noted that the 9th-10th century trading city of Sohar had formerly been surrounded by a wide belt of intensive agriculture. This apparently stretched far inland of the present day limits of irrigated cultivation and its estimated area of some 6,100 hectares was calculated to be four times that of the present day cultivation within the same length of coast. Furthermore, this figure is only 700 hectares less than the entire area of irrigated land to be found today along the Batina from the Emirates border in the north to Al Khaburah in the south. To supply this area with irrigation water would have required a sophisticated system of water supply and the possible yield of such a system assumes added significance today when the water resources of the Batina are proving to be a limiting factor in agricultural development.